KELAYAKAN MEDIA FLASH FLIPBOOK PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Nuruliah, Witri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to determine the feasibility of media flash flipbook on material biodiversity. The method used in this research was descriptive method with quantitative research technique. This media flash flipbook then was tested for feasibility by material experts and media experts. Experts material was lecturer of Biology Education Studies Program in FKIP Untan, a teacher of Biology Class X SMAN 1 Mandor and one Biology teacher class X SMA Swasta Yaraairo. Expert media wasÂ  lecturer of Physics Education Study Program in FKIP Untan, one lecturer ICT in IKIP PGRI Pontianak and one Information Technology and Communication teacher grade X SMAN 2 Ngarak. Based on the result of the validation analysis, media flash flipbook was validated feasible to be used as introduction media on material biodiversity by material experts with an average total value was 3.93 and media experts with an average total value was 3.70. Keywords: Feasibility, Flash flipbook, Biodiversity